Mechanical, durability, depolluting and electrical properties of multifunctional mortars prepared with commercial or waste carbon-based fillers. (10th May 2021) - Mobili, Alessandra; Belli, Alberto; Giosuè, Chiara; Pierpaoli, Mattia; Bastianelli, Luca; Mazzoli, Alida; Ruello, Maria Letizia; Bellezze, Tiziano; Tittarelli, Francesca
Highlights: Commercial and waste carbon-based fillers are compared in lime-based mixes. Waste fillers increase the compressive strength of lime-based mixes. Waste fillers decrease lime-based mixes water suction and increase VOCs adsorption. Waste fillers increase electrical conductivity and EMI SE of lime-based mixes. Waste fillers are a sustainable and cheap alternative for multifunctional mixes. Abstract: Carbon-based fillers from industrial wastes and commercial ones were compared to improve the properties of lime-based mixes. As commercial fillers, graphene nanoplatelets and activated carbon were used, whereas as industrial wastes a char obtained by the gasification of biomasses and a used foundry sand were chosen. Carbon-based wastes were found to be a good cost-effective alternative to commercial carbon based fillers to increase the compressive strength (of about 25%) and to reduce water capillary absorption (of about 50%) thanks to the paste refinement; to enhance depollution capacity (of about 25%) and increase both electrical conductivity (up to 65%) and electromagnetic shielding effectiveness (of about 6%) of the hardened compounds thanks to the carbon content.